A UWB MIMO slot antenna using defected ground structures for high isolation. Issue 5 (21st January 2020) - Wang, Enhao; Wang, Weimin; Tan, Xiaohua; Wu, Yongle; Gao, Jinchun; Liu, Yuanan
Abstract: In this article, a multiple‐input‐multiple‐output (MIMO) antenna with high isolation is proposed for ultrawideband (UWB) applications. The proposed MIMO antenna consists of two symmetric slot antenna elements with quasi F‐shaped radiators and L‐shaped open‐slots to increase impedance bandwidth. To improve isolation at the lower band, a decoupling network, composed of a narrow slot and a fork‐shaped slot, is introduced in the common ground. The measured results show that the proposed antenna provides high isolation of better than 20 dB over the operating band from 3 to 10.9 GHz. The performances of the UWB MIMO antenna in terms of radiation patterns, peak gain, envelope correlation coefficient, mean effective gain, and diversity gain are also studied.